An antibody cocktail targeting two different CD73 epitopes enhances enzyme inhibition and tumor control - Jin-Gen Xu; Shi Chen; Yang He; Xi Zhu; Yanting Wang; Zhifeng Ye; Jin Chuan Zhou; Xuanhui Wu; Lei Zhang; Xiaochen Ren; Huifeng Jia; Haijia Yu; et al. (Nature Communications)
Abstract CD73, an ectoenzyme responsible for adenosine production, is often elevated in immuno-suppressive tumor environments. Inhibition of CD73 activity holds great promise as a therapeutic strategy for CD73-expressing cancers. In this study, we have developed a therapeutic anti-human CD73 antibody cocktail, HB0045. HB0045 is a 1:1 mixture of two humanized monoclonal IgG1 antibodies (mAbs), HB0038 and HB0039. The cocktail not only harnesses the advantages of its parental mAbs in enzyme inhibition but also shows a significantly greater capability of promoting T cell proliferation in vitro. Structural analyses show that HB0045 effectively locks the CD73 dimer in a “partially open” non-active conformation through a double lock mechanism. In various animal models of syngeneic and xenograft tumors, HB0045 inhibits tumor growth more potently than the single mAbs. Collectively, our findings provide functional and structural insights into the mechanism of a CD73-targeting antibody cocktail.